2021
DOI: 10.1007/s00253-021-11332-9
|View full text |Cite
|
Sign up to set email alerts
|

An ADH toolbox for raspberry ketone production from natural resources via a biocatalytic cascade

Abstract: Raspberry ketone is a widely used flavor compound in food and cosmetic industry. Several processes for its biocatalytic production have already been described, but either with the use of genetically modified organisms (GMOs) or incomplete conversion of the variety of precursors that are available in nature. Such natural precursors are rhododendrol glycosides with different proportions of (R)- and (S)-rhododendrol depending on the origin. After hydrolysis of these rhododendrol glycosides, the formed rhododendro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(68 reference statements)
0
4
0
2
Order By: Relevance
“…The metabolism from RD to RK, which is considered to be related to leukoderma, may also be another cause of leukoderma. It has been reported that (R)-RD [19,21] in plants is converted to RK by ADH [22]. As ADH is a ubiquitously expressed enzyme that is also present in human skin [23], it is possible that RD, a secondary alcohol, is oxidized to RK.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism from RD to RK, which is considered to be related to leukoderma, may also be another cause of leukoderma. It has been reported that (R)-RD [19,21] in plants is converted to RK by ADH [22]. As ADH is a ubiquitously expressed enzyme that is also present in human skin [23], it is possible that RD, a secondary alcohol, is oxidized to RK.…”
Section: Discussionmentioning
confidence: 99%
“…After cleaving the ester bonds, the hydroxyl groups are oxidized to ketones by an alcohol dehydrogenase from Lactobacillus kefir (LK‐ADH) utilizing the cofactor NADP + with formation of NADPH (Scheme 2, step 2) [13a] . These ketones are then further oxidized to esters by the cyclohexanone monooxygenase (CHMO) variant M15 originally from the organism Acinetobacter calcoaceticus .…”
Section: Methodsmentioning
confidence: 99%
“…All enzymes used are well characterized and either easily recombinantly expressible in Escherichia coli or commercially available. [13] The enzyme cascade consists of four steps (Scheme 2) for modified PVA but can also be applied for unmodified PVA, starting at step 2. In step 1, ester bonds in the derivatized side chains are hydrolyzed by the commercially available lipase TL-IM resulting in unmodified PVA.…”
mentioning
confidence: 99%
“…Biocatalysis has taken on ever increasing importance for pharmaceutical process groups, including the design of enzyme cascades , to mediate key steps in building ever more complex molecular frameworks. ,,, Biocatalysis is becoming more and more versatile, and high-throughput assay systems have rendered directed evolution approaches more practical. Modern protein engineering methods allow for the combination of directed evolution approaches with in silico design of biocatalysts to enhance properties such as stability, substrate specificity, and enantioselectivity.…”
Section: Direct Enzymatic Screening Methodsmentioning
confidence: 99%